Management of Occupational Health and Safety During The Covid-19 Epidemic : Facts and Challenges - Wahyuni Diah Ekasari; Suharnomo Suharnomo; Intiyas Utami (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2021)
The Covid-19 epidemic has resulted in drastic changes as well as losses for the business world. This causes various companies to carry out occupational safety and health procedures for their employees. The purpose of this research is to dig deeper and understand the policies for managing occupational health and safety during the Covid-19 virus epidemic, implementation, challenges, and solutions. The number of informants in this study was ten people, including five subject informants and five triangulation informants. Data analysis was performed using qualitative data analysis methods with the critical phenomenology approach of the Stevick-Colaizzi-Keen model. The results of the analysis show that the management of occupational health and safety during the Covid-19 epidemic at the Rembang post office by implementing the 5M health protocol, namely wearing a mask, washing hands, social distancing, stay away from crowds, and reducing mobility has been carried out properly according to with a Circular from the Ministry of Manpower number B.5/51/AS.0202/I/2020, so as not to cause the spread of the Covid-19 virus cluster in the work environment of the Rembang branch Post office.